Determination of Precision of Triangulation by Error Propagation Law - Doğan, Nezir; Bettemir, Önder Halis (Fırat University, 2025)
Indoor location systems are widely used where the GPS positioning system does not provide location data. Social applications performed inside buildings, determining the location of living beings, the internet of things, automation in production, and robotic applications are examples for the implementation of indoor positioning. Aforementioned technique can provide sufficient location accuracy for the applications that requires the detection of which room or area people are in. On the other hand, obtaining sufficient accuracy requires laborious and expensive measurements for the indoor mapping applications. In the literature, effect of the accuracy of the distance measurement on the accuracy of position obtained by triangulation has not been discussed thoroughly. In this study to fill the aforementioned literature gap, precision of indoor positioning achieved by triangulation is estimated by the error propagation law. Uncertainties of the locations of three stations and uncertainties of the distances measured between the stations and the rover are taken as the input parameters of error propagation process. The partial derivatives of the triangulation equations of the error propagation equations with respect to the input parameters are calculated. Precision of the localization process conducted with the three station points placed on the sides of a virtual room is estimated at the joints of the formed regular mesh of a room with dimensions of 10x10 meters. It was concluded that the lowest amount of error occurred at the center of the room, which is the center of gravity of the station points, and that the amount of error caused by a station increased as the location is moved away from the center. Moreover, by examining the relative amount of error by taking the differences of the obtained error values with respect to their neighbors, it was observed that the positioning error and the change in the error size increased as it is moved away from the center of the room. Precision of positioning and the errors of the absolute dimensions of measured objects based on indoor mapping techniques are determined. This study also reveals the precision of a location obtained by triangulation conducted by a surveying device with a specific distance measurement accuracy, which can prevent the purchase of unnecessarily expensive surveying devices.

İç mekân konum sistemleri GPS konumlandırma sisteminin çalışmadığı bina içerisinde gerçekleştirilen sosyal uygulamalar için canlıların konumunu belirleme, nesnelerin interneti, üretimde otomasyon ve robotik uygulamalar amacıyla yaygın olarak kullanılmaktadır. Kişilerin hangi odada veya bölgede olduğunu belirleyen uygulamalarda yeterli konum hassasiyeti kolaylıkla sağlanabilirken iç mekânın haritalanmasını amaçlayan uygulamalarda oldukça zahmetli ve pahalı ölçümlerin yapılmasını gerektirmektedir. Literatürde kullanılan alıcıların mesafe ölçme hassasiyetine bağlı olarak elde edilecek konum hassasiyetini inceleyen yeteri kadar çalışma bulunmamaktadır. Belirtilen literatür boşluğunu gidermek için bu çalışmada üçgenleme yöntemi ile gerçekleştirilen iç mekân konumlandırmasının hassasiyeti hata yayılma kanunu ile tahmin edilmiştir. Hata yayılmanın girdi parametreleri olarak üç adet istasyonun konumlarındaki belirsizlik ve istasyonlar ile gezici arasında ölçülen mesafelerin belirsizlikleri alınmıştır. Hata yayılma kanununun uygulanması için üçgenleme denklemlerinin girdi parametrelerine göre kısmi türevleri hesaplanmıştır. Yöntemin uygulanabilmesi için boyutları 10x10 metreden oluşan sanal bir odanın kenarlarına yerleştirilmiş üç adet istasyon noktasından odanın düzenli aralıklı ızgaranın düğüm noktaları üzerinde yapılacak konum belirleme işleminin hassasiyeti hesaplanmıştır. En düşük hata miktarının istasyon noktalarının ağırlık merkezi olan odanın orta bölgesinde gerçekleştiği, bir istasyondan uzaklaşıldığında istasyondan kaynaklanan hata miktarının arttığı sonucuna varılmıştır. Ayrıca elde edilen hata değerlerinin komşuluklarına göre farkları alınarak göreceli hata miktarı incelenerek odanın merkezinden uzaklaşıldığında konumlandırma hatasının ve hata büyüklüğündeki değişimin arttığı gözlemlenmiştir. Bu çalışma sonucunda iç mekân konumlandırmaya bağlı olarak yapılacak haritalandırma ve rölöve çalışmalarının doğruluğu ve ölçülen cisimlerin mutlak boyutlarının hataları belirlenmiştir. Çalışma ayrıca bir ölçme cihazının mesafe hassasiyetine göre üçgenleme hassasiyetini de ortaya çıkardığı için gereksiz pahalılıkta ölçme cihazı alınmasının önüne geçebilecektir.
Üçgenleme ile Konumlandırmanın Hassasiyetinin Hata Yayılma Kanunu ile Belirlenmesi
Keywords: Geomatic Engineering (Other); Jeomatik Mühendisliği (Diğer)